A membrane-less electrolyzer for hydrogen production across the pH scale1. Issue 7 (1st July 2015) - H. Hashemi, S. Mohammad; Modestino, Miguel A.; Psaltis, Demetri
<x xml:space="preserve">Abstract</x> For the first time, a membrane-less electrolyzer has been demonstrated with the capability of non-flammable hydrogen production across the pH scale.